Faktor Faktor Yang Berhubungan Dengan Kunjungan Antenatal Care (ANC) di BPM Sri Rahayu Kec. Dolok Masihul Kab. Serdang Bedagai Tahun 2023 - Elfrida Trinita Sidauruk; Zulkarnain Batubara; Rosmega Rosmega (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: Factors that influence Antenatal Care (ANC) visits can reduce disability and maternal and fetal death rates. Antenatal Care is health care provided to pregnant women before and during pregnancy with the aim of early detection of maternal and fetal health problems. Objective: To determine factors that are related to Antenatal Care (ANC) visits. Method: This research uses an analytical survey with a cross sectional approach. The population taken was all pregnant women who visited antenatal care at PMB Sri Rahayu Dolok Masihul, namely 59 people. Sampling used a total sampling method of 59 people. Results: From the results of the univariate analysis, it was found that mothers who had ANC visits (86.7%), mothers who were highly educated (78.3%), mothers who were at low risk (86.7%), and mothers who did not work (84, 1%). The results of the chi square test showed a relationship between education (p value=0.000), age (p value= 0.008), employment (p value=0.013) and ANC visits. Suggestion: To continue to improve the quality of services for pregnant women and add counseling and education about the importance of antenatal care visits for pregnant women.